Pain severity and the economic burden of neuropathic pain in the United States: BEAT Neuropathic Pain Observational Study - Schaefer C; Sadosky A; Mann R; Daniel S; Parsons B; Tuchman M; Anschel A; Stacey BR; Nalamachu S; Nieshoff E (Dove Medical Press, 2014)
Caroline Schaefer,1 Alesia Sadosky,2 Rachael Mann,3 Shoshana Daniel,4 Bruce Parsons,2 Michael Tuchman,5 Alan Anschel,6 Brett R Stacey,7 Srinivas Nalamachu,8 Edward Nieshoff9 1Covance Market Access Services Inc., Gaithersburg, MD, 2Pfizer, Inc., New York, NY, 3Covance Market Access Services Inc., San Diego, CA, 4Covance Market Access Services Inc., Conshohocken, PA, 5Palm Beach Neurological Center, Palm Beach Gardens, FL, 6Rehabilitation Institute of Chicago, Chicago, IL, 7Oregon Health and Science University, Portland, OR, 8International Clinical Research Institute, Overland Park, KS, 9Rehabilitation Institute of Michigan/Wayne State University, Detroit, MI, USABackground: As with many chronic conditions, patients with neuropathic pain (NeP) are high consumers of health care resources. However, limited literature exists on the economic burden of NeP, including its impact on productivity. The aim of this study was to characterize health care resource utilization, productivity, and costs associated with NeP by pain severity level in US adults.Methods: Subjects (n=624) with painful diabetic peripheral neuropathy, human immunodeficiency virus-related peripheral NeP, post-trauma/post-surgical NeP, spinal cord injury with NeP, chronic low back pain with NeP, and small fiber neuropathy were recruited during routine office visits to US community-based general practitioners and specialists. Clinicians captured clinical characteristics, NeP-related medications, and health care resource utilization based on 6-month retrospective medical chart review. Subjects completed questionnaires on demographics, pain/symptoms, costs, and productivity. Brief Pain Inventory pain severity scores were used to classify subjects by mild, moderate, or severe pain. Annualized NeP-related costs (adjusted for covariates) were estimated, and differences across pain severity groups were evaluated.Results: In total, 624 subjects were recruited (mean age 55.5±13.7 years; 55.4% male), and 504/624 (80.8%) reported moderate or severe pain. Statistically significant differences were observed across pain severity levels for number of comorbidities, prescription medications, physician office visits, and lost productivity (all P≤0.0001). At all pain severity levels, indirect costs were the primary cost driver. After adjusting for demographic and clinical variables, total mean (95% confidence interval [CI]) annualized direct medical costs to payers, direct costs to subjects, and indirect costs per subject were US$6,016 (95% CI 5,316–6,716), US$2,219 (95% CI 1,919–2,519), and US$19,000 (95% CI 17,197–20,802), respectively, with significant differences across pain severity levels.Conclusion: Subjects with NeP, mainly those showing moderate or severe pain, had significant associations between pain severity and NeP-related health care resource utilization, productivity, and costs. The economic burden, particularly indirect costs, was highest among those with severe pain and higher than previously reported in studies of specific NeP conditions. Keywords: burden of illness, neuropathic pain management, health care costs, health care resource use, productivity